Impact of Transformational Leadership on Psychological Empowerment and Job Satisfaction Relationship: A Case of Yemeni Banking - Al-Hosam, Asma Abdulwasea Mohammed; Ahmed, Shaheen; Ahmad, Fais Bin; Joarder, Mohd Hasanur Raihan (Binus Business Review, 2016)
The banking sector of Yemen is under threat due to the lack of confidence and trust of the prospective clients that hindered economic development of the country. The study aimed to measure a moderating effect of transformational leadership on employeesâ psychological empowerment and job satisfaction relationship so that attitudes of the Yemeni can be bumped towards banking. In this study, 160 employees were surveyed in different branches of four banks in Yemen. The data were analyzed in four stages namely, reliability and validity analysis, descriptive analysis, multivariate analysis, and hypotheses testing analysis. The study revealed a significant positive relationship between employeesâ psychological empowerment and transformational leadership towards their job satisfaction level. If the policy makers consider the findings and undertake necessary measures, the Yemeni banking is expected to be accelerated which will contribute to the economy of the country.